COD removal characteristics in air-cathode microbial fuel cells. (January 2015) - Zhang, Xiaoyuan; He, Weihua; Ren, Lijiao; Stager, Jennifer; Evans, Patrick J.; Logan, Bruce E.
Graphical abstract: Highlights: COD removal in air-cathode MFCs fit first-order kinetics. Current generation accelerated COD removal for both acetate and wastewater. COD removal rate constants for wastewater with current were higher than acetate. Current generation stopped before substrates were fully depleted. For acetate, coulombic efficiencies were inversely related to COD concentration. Abstract: Exoelectrogenic microorganisms in microbial fuel cells (MFCs) compete with other microorganisms for substrate. In order to understand how this affects removal rates, current generation, and coulombic efficiencies (CEs), substrate removal rates were compared in MFCs fed a single, readily biodegradable compound (acetate) or domestic wastewater (WW). Removal rates based on initial test conditions fit first-order kinetics, but rate constants varied with circuit resistance. With filtered WW (100 Ω), the rate constant was 0.18 h − 1, which was higher than acetate or filtered WW with an open circuit (0.10 h − 1 ), but CEs were much lower (15–24%) than acetate. With raw WW (100 Ω), COD removal proceeded in two stages: a fast removal stage with high current production, followed by a slower removal with little current. While using MFCs increased COD removal rate due to current generation, secondary processes will be needed to reduce COD to levels suitable for discharge.